Comparative study of non-covalent interactions between cationic N-phenylviologens and halides by electrochemistry and NMR: the halogen bonding effect. (20th July 2017) - Creste, Geordie; Groni, Sihem; Fave, Claire; Branca, Mathieu; Schöllhorn, Bernd
Abstract : Five N -phenylviologen (PV 2+ ) derivatives have been synthesized and their electrochemical behavior in the presence of halide anions has been studied. Further investigations were carried out by 1 H and 19 F NMR spectroscopy at different chloride concentrations. This is the first time a systematic study combines cyclic voltammetry and NMR spectroscopy in order to analyse the contribution of halogen bonding among the various non-covalent interactions between iodinated N -phenylviologens. The results show strong evidence for a significant "halogen bonding effect" in the interaction between halides and the iodo-tetrafluoro-phenylviologenPV 2+ -C6 F4 I . A significant influence of halogen bonding on reduction potentials of the novel halogen bond donorPV 2+ -C6 F4 I has been evidenced resulting in the first example of "inverse redox switching" of an XB-donor being partially deactivated upon reduction. Furthermore the particular binding properties of the perfluorinated derivativePV 2+ -C6 F5 towards chloride are discussed considering a possible contribution of π–anion interaction in solution.